Taming Log Files From Game/Simulation‐Based Assessments: Data Models and Data Analysis Tools. Issue 1 (29th March 2016) - Hao, Jiangang; Smith, Lawrence; Mislevy, Robert; von Davier, Alina; Bauer, Malcolm
Abstract: Extracting information efficiently from game/simulation‐based assessment (G/SBA) logs requires two things: a well‐structured log file and a set of analysis methods. In this report, we propose a generic data model specified as an extensible markup language (XML) schema for the log files of G/SBAs. We also propose a set of analysis methods for identifying useful information from the log files and implement the methods in a package in the Python programming language, glassPy. We demonstrate the data model and glassPy with logs from a game‐based assessment, SimCityEDU. Abstract : Report Number: ETS RR‐16–10